THE COVID RETIREMENT BOOM: DID DATA COLLECTION DISRUPTION PLAY A ROLE? - Thompson, Daniel (Social Security Bulletin, 2025)
One of the most frequently discussed labor market patterns of the COVID-19 pandemic was an increase in retirements, particularly among persons aged 65-74. This article considers whether the measured rise in the retired share of the population reflects changes to Current Population Survey (CPS) data collection procedures that were necessitated by public health efforts. These changes contributed to a sharp increase in survey nonresponse from February to June 2020. The largest apparent growth in the retired share of the population occurred in March 2020, when data collection procedures changed and nonresponse started to increase. However, that survey's reference period preceded the declaration of COVID-19 as a pandemic and the implementation of public health measures, suggesting that nonresponse bias may have driven the CPS-measured increase in the retired share of the population. Other surveys and data sources show little evidence of an increase in retirements during the pandemic.